Diurnal Cycle of a Heavy Rainfall Corridor over East Asia - Chen, Guixing; Sha, Weiming; Iwasaki, Toshiki; Wen, Zhiping (Monthly weather review, 2017)
Moist convection occurred repeatedly in the midnight-to-morning hours of 11–16 June 1998 and yielded excessive rainfall in a narrow latitudinal corridor over East Asia, causing severe flood. Numerical experiments and composite analyses of a 5-day period are performed to examine the mechanisms governing nocturnal convection. Both simulations and observations show that a train of MCSs concurrently developed along a quasi-stationary mei-yu front and coincided with the impact of a monsoon surge on a frontogenetic zone at night. This process was regulated primarily by a nocturnal low-level jet (NLLJ) in the southwesterly monsoon that formed over southern China and extended to central China. In particular, the NLLJ acted as a mechanism of moisture transport over the plains. At its northern terminus, the NLLJ led to a zonal band of elevated conditionally unstable air where strong low-level ascent overcame small convective inhibition, triggering new convection in three preferred plains. An analysis of convective instability shows that the low-tropospheric intrusion of moist monsoon air generated CAPE of ~1000 J kg −1 prior to convection initiation, whereas free-atmospheric forcing was much weaker. The NLLJ-related horizontal advection accounted for most of the instability precondition at 100–175 J kg −1 h −1 . At the convective stage, instability generation by the upward transport of moisture increased to ~100 J kg −1 h −1 , suggesting that ascending inflow caused feedback in convection growth. The convection dissipated in late morning with decaying NLLJ and moisture at elevated layers. It is concluded that the diurnally varying summer monsoon acted as an effective discharge of available moist energy from southern to central China, generating the morning-peak heavy rainfall corridor.